SHOGUN: An Integrated Dashboard for Vulnerability Analysis via Internet-Wide Search Engines - Matos, Isabelle; Ponce, Lucas M; Cunha, Igor; Almeida, Pedro; Fazzion, Elverton; Cunha, Ítalo; Hoepers, Cristine; Steding-Jessen, Klaus; Chaves, Marcelo H. P. C.; Guedes, Dorgival; Meira Jr, Wagner (Anais Estendidos do Simpósio Brasileiro de Cibersegurança (SBSeg); 2026: Anais Estendidos do XXVI Simpósio Brasileiro de CibersegurançaDO - 10.5753/sbseg_estendido.2026.33700, 2026)
The increasing exposure of digital assets on the Internet demands efficient solutions for identifying and continuously monitoring vulnerabilities. While search engines like Shodan provide a targeted retrieval of exposure data, longitudinal risk assessment requires extensive data preparation. To bridge this gap, we present SHOGUN, an interactive dashboard engineered for the multidimensional analysis of internet-wide vulnerability data. Built upon a decoupled architecture, our tool abstracts raw search engine dumps into structured analytical datasets. The tool features a reactive web interface that combines geospatial and statistical visualizations with a cross-view drill-down navigation model, allowing security analysts to transition from macro-level network overviews to granular, asset-level forensic investigations.